1990
DOI: 10.1111/j.1558-5646.1990.tb05247.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Female Body Size in Red‐winged Blackbirds: The Effects of Timing of Breeding, Social Competition, and Reproductive Energetics

Abstract: We examined opposing selective forces on female body size in the sexually dimorphic red-winged blackbird: social competition favoring larger females, and energetic advantages favoring smaller females. Downhower proposed that selection might drive female birds to be smaller than the optimum for survival, if smaller females were able to exceed their energetic requirements for self-maintenance earlier in the season and therefore breed earlier. Since in most birds the earliest breeders fledge the most young, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
(27 reference statements)
3
31
1
Order By: Relevance
“…This hypothesis predicted directional selection favoring smaller females. We did not find this pattern, nor did we find that larger females survived better than smaller ones (Langston et al 1990). …”
Section: Patterns Ofselection On Sizecontrasting
confidence: 44%
See 1 more Smart Citation
“…This hypothesis predicted directional selection favoring smaller females. We did not find this pattern, nor did we find that larger females survived better than smaller ones (Langston et al 1990). …”
Section: Patterns Ofselection On Sizecontrasting
confidence: 44%
“…Both dominance and bioenergetic constraints may favor large body size during winter and early spring. For instance, larger males are (1) dominant over smaller males (and likely females) and will therefore win most disputes for food (Searcy 1979c;Eckert and Weatherhead 1987a; see also Langston et al 1990 for similar results with female red-winged blackbirds); and (2) capable of enduring unfavorable winter weather conditions better than smaller birds, owing to the reduced surface-area-to-volume ratio oflarger birds (e.g., James 1970). Early arrival may be particularly advantageous ifthese males have a better chance of acquiring territories simply by being first on the territory rather than by direct contests (Myers 1981;Shutler and Weatherhead 1992).…”
Section: Size and Selection: Alternativementioning
confidence: 99%
“…1a-c). Evidence of stabilizing selection on body mass was not found in female lesser scaup (Aythya affinis; Rotella et al 2003), but was reported in herring gulls (Larus argentatus; Monaghan and Metcalfe 1986) and red-winged blackbirds (Agelaius phoeniceus; Langston et al 1990;Weatherhead and Clark 1994). However none of these studies used com- Table 3 bined capture-recapture-band-recovery models in their analyses.…”
Section: Body Conditionmentioning
confidence: 90%
“…Body size (Murphy 1986;Langston et al 1990), age (Hochachka 1990;Burger et al 1996), experience (Nager and van Noordwijk 1995) and foraging skills (Winkler and Allen 1996) may aect condition indices. However, these eects may be mediated through more proximate factors like health status and immune function.…”
Section: Introductionmentioning
confidence: 99%